2013
DOI: 10.1093/cid/cit058
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Predictors and Incubation Period of AIDS-AssociatedPenicillium marneffeiInfection in Ho Chi Minh City, Vietnam

Abstract: Our findings suggest that humidity is the most important environmental predictor of P. marneffei admissions, and may drive exposure by facilitating fungal growth or spore release in the environment. In addition, it appears that a high proportion of penicilliosis patients present to the hospital with primary disseminated infection within 3 weeks of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 17 publications
6
40
1
Order By: Relevance
“…83 Incidence increases 30-50% during the rainy months, 76,84 and can be predicted by humidity levels. 85,86 T marneffei has been isolated from bamboo rat faeces and soil samples within bamboo rat burrows, 87,88 and T marneffei DNA detected in elephant-associated soil. 89 Collectively, these epiecological data suggest an interplay among multiple environmental reservoirs involving soil, plants, and animals, in which bamboo rats may be exploited by T marneffei to expand its biomass and biogeography.…”
Section: Ecology and Transmissionmentioning
confidence: 99%
“…83 Incidence increases 30-50% during the rainy months, 76,84 and can be predicted by humidity levels. 85,86 T marneffei has been isolated from bamboo rat faeces and soil samples within bamboo rat burrows, 87,88 and T marneffei DNA detected in elephant-associated soil. 89 Collectively, these epiecological data suggest an interplay among multiple environmental reservoirs involving soil, plants, and animals, in which bamboo rats may be exploited by T marneffei to expand its biomass and biogeography.…”
Section: Ecology and Transmissionmentioning
confidence: 99%
“…4 Previous studies have indicated that T. marneffei is the third most common agent of clinical infections among patients with acquired immune deficiency syndrome in Southeast Asia, after Mycobacterium tuberculosis and Cryptococcus neoformans, and is associated with increasing mortality rates. 2,5 In addition, T. marneffei infection occurs in patients with underlying immune defects without HIV infection. [6][7][8] Recurrent, refractory, and disseminated T. marneffei infections are probably due to immune dysfunction in hosts, but the mechanisms are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with this infection who are encountered in the USA have almost always either traveled in these areas or lived there (38-42). Penicilliosisis emerging as one of the most common opportunistic infections in Asian patients with AIDS (39, 42).…”
Section: The Differential Diagnosis Of Yeastmentioning
confidence: 99%
“…Patients with this infection who are encountered in the USA have almost always either traveled in these areas or lived there (38-42). Penicilliosisis emerging as one of the most common opportunistic infections in Asian patients with AIDS (39, 42). Patients with this infection who are HIV-negative often have other immunocompromising conditions such as hematologic malignancies, autoimmune diseases, malnutrition or other debilitating infections, and this infection has rarely been described in immunocompetent persons.…”
Section: The Differential Diagnosis Of Yeastmentioning
confidence: 99%